AUV ABYSS sensor data (CTD, Fluorometer, turbidity) and vehicle performance for dives during RV METEOR cruise M198 - Morelia Urlaub; Ulrike Lomnitz; Emanuel Wenzlaff (PANGAEA, 2024)
A total of seven missions of the autonomous underwater vehicle (AUV) Abyss was performed February 2024 around Mount Etna, Europe extquotesingles largest active volcano, during RV METEOR cruiseM198. Each dive lasted several hours and recorded information for a number of sensors including CTD (Seabird SBE49FastCAT) and ECO (=combined fluorometer and turbidity senso; Wetlabs FLNTU/0712017) . The sensor data is recorded in separate files for each dive. The vehicles performance under water and core functions (roll, pitch, heading, power use, and many others) are recorded in the STATE file of each dive.